Autistic pupils' experiences in primary and post-primary schools: A scoping review and consultation with autistic pupils in Ireland - Lynam, Aoife (My University, 2025)
Background and aims: Autistic pupils have the right to be heard in matters concerning their education and to be active agents in shaping their school experiences. Despite this, educational policies and research have rarely included the voices of autistic children, failing to identify what they consider to be beneficial and meaningful in their own education. This study aimed to (i) summarise existing literature exploring autistic pupils' experiences at school from their own perspectives and (ii) identify gaps for future research through a consultation with autistic pupils. Methods: A scoping review was conducted to identify studies exploring first-person accounts of autistic pupils' school experiences (primary and secondary; aged 4-18 years) published between 2005 and 2023. Thematic analysis was conducted to identify overarching thematic categories across the included studies. Review findings were discussed through a consultation with a Child and Youth Advisory Group (CYAG) comprised of autistic pupils in Ireland (N = 3), to seek feedback and inform a future research agenda. Main contribution: Thirty-six studies were included in the review and six themes were identified: Experiences of feeling misunderstood, of bullying and masking, of feeling excluded, of anxiety, of sensory needs in school, and of being overwhelmed during transitions. Consultation with the CYAG highlighted that these six themes were consistent with autistic pupils' experiences but that reports of positive experiences were missing in the literature. Conclusions: This study identified several gaps in the literature on the school experiences of autistic pupils, based on both the scoping review and consultation with the CYAG. While the CYAG validated the themes identified in existing literature, there is a need for greater diversity in the samples included and increased focus on the potential positive aspects of the school experience. Implications. These findings have important research implications. In particular, further studies are needed with autistic pupils at primary school level, including those who are minimally or non-speaking, as well as ensuring pupils with positive school experiences are also represented. Findings also highlight the need for continued collaboration with autistic pupils themselves in matters concerning their education.
PUBLISHED
Keywords: Autism; child voice; lived experience; school-age children; scoping review; Inclusive Society; Inclusive Education; Autistic Spectrum disorders